Marine ammonification and carbonic anhydrase activity induce rapid calcium carbonate precipitation. (15th December 2018) - Krause, S.; Liebetrau, V.; Löscher, C.R.; Böhm, F.; Gorb, S.; Eisenhauer, A.; Treude, T.
Abstract: During Earth's history, precipitation of calcium carbonate by heterotrophic microbes has substantially contributed to the genesis of copious amounts of carbonate sediment and its subsequent lithification. Previous work identified the microbial sulfur and nitrogen cycle as principal pathways involved in the formation of marine calcium carbonate deposits. While substantial knowledge exists for the importance of the sulfur cycle, specifically sulfate reduction, with regard to carbonate formation, information about carbonate genesis connected to the microbial nitrogen cycle is dissatisfactory. In addition to the established pathways for carbonate mineral formation, also the potential of microbial carbonic anhydrase, a carbonate-relevant, zinc-containing enzyme, is receiving currently increased attention. However, also in this field knowledge is scarce and fragmentary. Here we demonstrate microbial carbonate precipitation as a direct result of the interplay between the microbial nitrogen cycle and a microbially produced enzyme. Using Alcanivorax borkumensis as a model organism, our experiments depict precipitation of a peloidal carbonate matrix within days to weeks, induced by simultaneous ammonification and extracellular carbonic anhydrase activity. The precipitates show similar morphology, mineralogy, δ 44/40 Ca, and δ 88/86 Sr to analogs of modern carbonate peloids. The obtained Sr/Ca partition coefficient DSr showed no clear deviation from inorganic carbonate phases, indicating that microbially mediated carbonate precipitation, indeed, follows the principles of physico-chemical precipitation. The observed relative enrichment of the precipitates in zinc might help to constrain zinc variations in natural carbonate archives. Our study demonstrates that ammonification, due to intense microbial organic matter degradation, and carbonic anhydrase may play a substantial role for calcium carbonate precipitation in paleo- and recent shallow marine environments.